Aktualisasi Nilai-Nilai Moderasi Beragama dalam Buku Pelajaran Al-Qur’an Hadis Madrasah Ibtidaiyah - Alnashr, M Sofyan; Hakim, Muh. Luthfi (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
The plural and multicultural reality of Indonesia requires a moderate and tolerant attitude in religion. The values of religious moderation must be taught from school age and actualized in learning and daily life. This study aims to describe the actualization of religious moderation values contained in the Quran Hadith textbook at the Madrasah Ibtidaiyah level. This research is a literature research with the object of the research of the Quran Hadith textbooks from grade 3 to grade 6 which teach short letters from the Quran. Data analysis uses interpretative with contextual interpretation of Quranic verses. The results showed that the values of religious moderation contained in the MI Quran Hadith book are values of Civilization (Ta'addub), Exemplary (Qudwah), Citizenship and nationality (Muwaṭanah), Taking the middle way (Tawassuṭ), Balanced (Tawāzun), Straight and firm (I'tidāl), Equality (Musāwah), Deliberation (Syūra), Tolerance (Tasāmuh), and Dynamic and innovative (Tathawwur wa Ibtikâr). The actualization of religious moderation values for MI students is through contextualizing values in learning and instilling moderation values in social media. The development of information technology is followed by the entry of various cultures and ideologies that sometimes conflict with religious teachings, therefore the value of moderation must be actualized in every child's daily activities.